الأساليب النبوية في الدعوة العائلية (نوح-إبراهيم -محمد) عليهم الصلاة والسلام أنموذجا - هراوة, منى; الأطرش, قدرية; لطرش, حياة (University of Eloued-جامعة الوادي, 2022)
ملخص الدراسة : هذا البحث موسوم بــــــ: الأساليب النبوية في الدعوة العائلية أنبياء الله ( نوح إبراهيم محمد) عليهم الصلاة والسلام أنموذجا والاشكالية الرئيسية لهذا البحث هي : ما هي الأساليب الدعوية التي انتهجها أنبياء الله نوح وإبراهيم ومحمد عليهم الصلاة والسلام في دعوتهم لأقاربهم؟ وقد اشتمل بحثنا على مبحثين أساسيين ؛ جانب نظري وتطرقنا فيه إلى مفهوم الأساليب النبوية ثم مفهوم الدعوة العائلية (دعوة الأقارب)، و أبرزنا كذلك أساليب دعوة الأنبياء في القرآن وبَيَّنَا أيضا أسباب عناية الأنبياء بتوجيه الدعوة إلى الأقارب ، ثم تخصصنا في موضوع بحثنا وهو أساليب دعوة الأنبياء (نوح، إبراهيم، محمد) لأقاربهم، وفيه تم التعريف بأنبياء الله (نوح، إبراهيم، محمد ) عليهم الصلاة والسلام ، ثم توسعنا في ذكر الأساليب الدعوية المختلفة لأنبياء الله (نوح، إبراهيم، محمد) لأقاربهم، ففي دعوة الوالد نجد دعوة إبراهيم لأبيه، وفي دعوة الأولاد نجد دعوة نوح وإبراهيم لأبنائهم، وكذلك نجد دعوة نبينا محمد صلى الله عليه وسلم لبناته وزوجاته، وسائر الأقربين والعشيرة تنفيذاً لأمر الله سبحانه وتعالى. وتوصلنا في هذا البحث إلى النتائج التالية : - أن الدعوة إلى الله واجبة على كل مسلم ومسلمة وخاصة إذا تعلق الأمر بالأقارب فهم أول من يُطلَبُ لهم النجاة من النار . - دعوة الأقارب وتوجيههم للخير من أفضل الصلة وبالخصوص إذا كان ذلك مع الأهل والوالدين فيعتبر دعوتهم من أبر البر والإحسان إليهم. - رغم كل الابتلاءت والتحديات والصَّد التي وجدها أنبياء الله (نوح وإبراهيم ومحمد) عليهم الصلاة والسلام من أقاربهم إلا أنهم كانوا يسعون في تنويع أساليبهم الدعوية حتى يخرجوا أقاربهم من الشرك والجهل والضلال وهدايتهم للحق والإيمان والخير . وبعد الوقوف على عدد من النماذج الدعوية وبيان ما فيها من الأساليب نخرج بالتوصيات التالية: - يجدر التأمل في هاته الأساليب النبوية والسير على نهجها وتفعيلها في دعوتنا لأقاربنا وتجسيدها واقعا ملموسا وسلوكا متبعا في شتى المجالات . - على الداعية أن يتحلى بصفات الأنبياء عند قيامه بالدعوة كالصبر ورحابة الصدر وتحمل كل ما يصدر من المدعو بكل ايجابية وذلك لأنه معرّض للخطر والإيذاء في دعوته إلى الله . الكلمات المفتاحية : الأساليب النبوية – الدعوة العائلية – الأقارب – الأنبياء – نوح – إبراهيم – محمد Abstract: This research is tagged with: The Prophetic Methods in the Family Call, the Prophets of God (Noah Ibrahim Muhammad), may blessings and peace be upon them, as a model. The main problem of this research is: What are the advocacy methods adopted by the prophets of God, Noah, Abraham and Muhammad, peace and blessings be upon them, in calling their relatives? In the first chapter, we discussed we focused on the concept of family calling (calling relatives) , and The concept of methods of calling the prophets and The method of setting proverbs, the method of removing suspicions, the method of stories, and the method of argument and proof. As for the second chapter, and, as it appears through the Qur’anic verses that there is a clear indication that the Holy Qur’an directed the prophets, peace be upon them, to the necessity of taking care of the guidance, In this research we reached the following results: The call to God is obligatory for every Muslim man and woman, especially when it comes to relatives, as they are the first to be asked to be saved from Hellfire. Inviting relatives and directing them to goodness is one of the best connections, especially if it is with family and parents. Despite all the trials, challenges and repulsions that the prophets of God (Noah, Abraham and Muhammad) found from their relatives, they were trying to diversify their methods of advocacy in order to get their relatives out of polytheism, ignorance and misguidance and guide them to truth, faith and goodness. After examining a number of advocacy models and explaining their methods, we come up with the following recommendations: It is worth contemplating these prophetic methods and following their approach and activating them in our invitation to our relatives and embodying them as a tangible reality and behavior followed in various fields. The caller must possess the qualities of the prophets when performing the call, such as patience and openness of heart, and bear everything that comes from the invited person in all positivity, because he is exposed to danger and harm in his call to God. key words: Prophetic methods - family invitation - relatives - prophets - Noah - Abraham - Muhammad
مذكرة ماستر
Keywords: الأساليب النبوية - الدعوة العائلية - الأنبياء; Prophetic methods - family invitation - prophets